Efektivitas konseling cognitive behavior teknik latihan asertif untuk mereduksi perilaku merokok pada siswa sekolah menengah atas - Candrapatni, Komang; Gading, I Ketut; Dharmayanti, Putu Ari (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2024)
This study aims to determine the application of cognitive behavior counseling techniques of assertive training to reduce smoking behavior in high school students. The method used in this study is experimental. Sampling using purposive sampling technique. Data collection collected a smoking behavior questionnaire. The data analysis technique used parametric statistical analysis, namely by using the Paired-Sample T-Test with the help of the SPSS For Windows version 25.00 program. This research method aims to determine the effect of cognitive behavior counseling on assertive training techniques to reduce smoking behavior in high school students. The design of this study was the Pretest-Postest Control Group Design which was carried out on students in the control class and the experimental class. This research focuses on the changes produced by cognitive behavior counseling, assertive practice techniques to reduce smoking behavior in high school students with the data collection technique used, namely a questionnaire. Based on the significance test, it was found that the significance value was 0.000 where 0.000 ˂ 0.05, where the Application of Cognitive Behavior Counseling Assertive Training Techniques is Effective for Reduce Smoking Behavior in High School Students.